KORUPSI, ANGGARAN, DAN MASYARAKAT: SEBUAH CINTA TERLARANG - Henni Mande (AkMen JURNAL ILMIAH, 2017)
The writing aims to analyze the extent of the role of society in the occurrence of corruption. The method used is qualitative descriptive. The findings of this research, first of all, is that the community plays a role in corruption because community behavior in the form of "forbidden love" leads to budget corruption and it is difficult to abandon the behavior. Secondly, society plays a role in corruption through its relationship with legislative, government, bureaucracy and culture.